Toribio de Mogrovejo, Rome and the creation of a diocesan government scheme in South America - López Lamerain, Constanza (2021)
In the 16th century, from the Archbishopric of Lima, a model of metropolitan ecclesiastical government began to be created that would provide a clear path to follow for the nascent dioceses of the ecclesiastical province of Peru. In part this was modeled after the provincial councils held in the City of Kings, and even more after the reception of the Council of Trent. With Toribio de Mogrovejo at the head of the archbishopric of Lima, the ecclesiastical structures were strengthened under the leadership of the bishops, key figures of the Tridentine reform and the government of the Universal Church. Mogrovejo followed the guidelines of the Tridentine in detail, which is evident by the fluid communication that he maintained with the Holy See during his government, presenting information and doubts about the application of canon law for his province in order to strengthen his metropolitan government and his episcopal jurisdiction.